Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 5 - Section 5.2 - Multiplication of Polynomials - Exercise Set - Page 339: 112



Work Step by Step

The square of a binomial sum is: $(A-B)^2=A^2-2AB+B^2$. Hence here: $\frac{(5x-3)^6}{(5x-3)^4}=(5x-3)^{6-3}=(5x-3)^2=(5x)^2-2\cdot5x\cdot3+3^2=25x^2-30x+9$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.